Preparation of g-C3N4/ZIF-8/PVDF–modified Li anode for all-solid-state Li metal batteries - Walle, Kumlachew Zelalem; Wu, Yi–Shiuan; Wu, She–Huang; Chien, Wenchen; Chang, Jengkuei; Jose, Rajan; Yang, Chun Chen (Elsevier Ltd, 2024)
All-Solid-state lithium metal batteries (ASSLMBs) are promising next-generation energy storage devices. However, the formation of lithium (Li) dendrites in ASSLMBs limits their applications. In this study, we used an inorganic/organic mixture of graphitic carbon nitride (g-C3N4), zinc-based Zeolitic Imidazolate Framework-8 (ZIF-8), and poly(vinylidene difluoride) (PVDF)—g-C3N4/ZIF-8/PVDF (g-CNZP)—to modify the surface of a lithium metal anode (LMA). The 2032-type coin cell was assembled based on a lithium Nafion (LiNf)–coated NCM811 (denoted as LiNf@NCM811) cathode, inorganic/organic mixture modified Li metal anode (LMA) (denoted g-CNZP@Li), and a LiNf-coated Li6.05Ga0.25La3Zr2O11.8F0.2 (LiNf@LG0.25LZOF) filler in bilayer hybrid solid electrolyte (Bi-HSE). The coin cell was charged between 2.8 and 4.2 V at 0.5C exhibited an initial specific discharge capacity of 134.45 mAh g−1 and retained 86.1 % of its capacity after 280 cycles at 30 °C. The average coulombic efficiency of the cell was approximately 99.8 %. Furthermore, the high-voltage (2.8–4.5 V, at a rate of 0.2C) result also delivered an initial specific discharge capacity of 194.3 mAh g−1 and, after 100 cycles, maintained 81.8 % of its initial capacity at room temperature. The presence of the nanosheet/nanoparticle composite coating material on the LMA surface suppressed Li dendrite growth and enhanced the compatibility between the LMA and Bi-HSE membrane. In addition, the in-situ formation of Li3N on the solid electrolyte interface (SEI) layer improved the ionic conductivity and ensured intimate interfacial contact during cycling. Therefore, these novel bi-layered fabrication strategies for obtaining hybrid/composite solid electrolyte membranes and modifying LMA surfaces via 2D g-C3N4 material with ZIF-8 MOFs and PVDF composites appear to have applicability in the preparation of very safe high-voltage cathodes for ASSLMBs.